1997
DOI: 10.1029/96jd02995
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the independent pixel approximation for satellite estimates of oceanic boundary layer cloud optical depth

Abstract: . The random error decreases as the averaging scale increases, but error due to inhomogeneity remains. At the 60 km scale the average •rror is about 6% for high Sun, 2% for low Sun. Individual scenes, however, have retrieved optical depth errors as high as 45% due to horizontal radiative transport. The ability to retrieve higher statistical moments of the frequency distribution of optical depth is also assessed. Sigma, (a), the standard deviation of 7-, is retrieved quite well up to a point, then is underestim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 27 publications
2
55
0
Order By: Relevance
“…Errors due to cloud heterogeneity have been analyzed mainly in the context of satellite remote sensing. Varnai (1998) and Chambers et al (1997) observed that the cloud spatial reflectance variation is smoother than variations in τ c . They hypothesized that optically thicker clouds would scatter more light to their thinner neighboring clouds, causing the thinner clouds to appear brighter and thicker (looking from space), while the thinner clouds would scatter less light to the thicker clouds, making them appear darker and thinner than expected for a homogeneous cloud scene.…”
Section: Discussionmentioning
confidence: 99%
“…Errors due to cloud heterogeneity have been analyzed mainly in the context of satellite remote sensing. Varnai (1998) and Chambers et al (1997) observed that the cloud spatial reflectance variation is smoother than variations in τ c . They hypothesized that optically thicker clouds would scatter more light to their thinner neighboring clouds, causing the thinner clouds to appear brighter and thicker (looking from space), while the thinner clouds would scatter less light to the thicker clouds, making them appear darker and thinner than expected for a homogeneous cloud scene.…”
Section: Discussionmentioning
confidence: 99%
“…For observations with a high spatial resolution, such as the Thematic Mapper onboard the Landsat satellites, cloud heterogeneities at scales larger than the sensor spatial resolution yield a breakdown of IPA (Barker and Liu, 1995;Chambers et al, 1997). In contrast, satellite observations with a lower spatial resolution cannot resolve heterogeneous cloud structures within a pixel, introducing significant biases in retrieved τ and r eff (Cahalan et al, 1994a;Marshak et al, 2006;Zhang and Platnick, 2011;Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 94%
“…During conditions of broken cloud cover, however, this approximation is especially limited. In an attempt to investigate the 3-D effects of clouds, several recent model studies (Stephens et al, 1990;Chambers et al, 1997) have mainly examined the change in radiance and actinic flux values at fixed locations due to inhomogeneities. Although the 3-D effect of clouds on the actinic flux is solvable, the major challenge that one is faced with is the specification of cloud input (Kylling et al, 2005).…”
Section: Comparison Ofmeasurements With Rt Model Calculations Of Jhonmentioning
confidence: 99%